Determinants of Capital Budgeting Practices and Risks Adjustment among Cambodian Companies - M. Maáji, Muhammad; Barnett, Casey (Archives of Business Research, 2019)
This study uses a sample survey to analyse the capital budgeting practices of Cambodian companies in the manufacturing sector. The findings show that payback period, NPV, discounted payback period and accounting rate of return are the most popular evaluation techniques. The study also finds that interest rate risk as well as business cycle risk are mainly adjusted with a discount rate, and the commonly used method for calculating cost of capital is the after tax cost of debt and the weighted average cost of capital (WACC). Furthermore, the finding suggests that the longer the existence of a company, the more likely for it to use NPV method. The finding also reveals that the higher the amount of capital investment, the more it is likely to use the NPV method, while the smaller the amount of capital investment, the more likely the payback method will be used. With higher educational background, NPV and ARR are most likely the methods to be used in capital budgeting among the Cambodian firms.